Spatial Variability of CO2 Emissions from Newly Exposed Paraglacial Soils at a Glacier Retreat Zone on King George Island, Maritime Antarctica - Thomazini, Andre; Teixeira, Daniel De Bortoli [UNESP]; Gabrig Turbay, Caio Vinicius; La Scala, Newton [UNESP]; Schaefer, Carlos Ernesto G. R.; Mendonca, Eduardo De Sa (Wiley-Blackwell, 2014)
Thawed soils in Antarctica represent organic carbon (C) reservoirs with great potential to increase the net losses of CO2 to the atmosphere under climate change scenarios. This study spatially zones CO2 emissions from soil and vegetation along a transect in front of the retreating margin of Ecology Glacier in Admiralty Bay, King George Island, South Shetlands, near the Polish Antarctic station Henryk Arctowski. Two experiments were carried out to determine soil respiration: (1) a transect of 150 measuring points spaced 1m apart, statistically analysed with split moving windows, identified three regions with different patterns of CO2 emissions; (2) a survey with three grids containing 60 sampling points, with a minimum distance between points of 0.30m, totalling 2.7x1.5m, in each of the identified locations. The survey showed that CO2 emission rates decreased (from 2.38 to 0.00 mu molm(-2)s(-1)) and soil temperature at 5cm depth increased (from 1.9 to 7 degrees C) near the glacier. The site farthest from the glacier provided an emission 3.5 times higher than the closest site. The spatial variability of CO2 emissions decreased with distance from the glacier. Soil development and vegetation are identified as key drivers of CO2 emissions. Soil formation and vegetation growth increased with longer exposure since deglaciation, leading to enhanced homogeneity of CO2 emissions, independent of permafrost occurrence and stability. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: permafrost; soil organic matter; organic carbon